ONSET PENGELUARAN KOLOSTRUM PERSALINAN NORMAL LEBIH CEPAT DARIPADA PERSALINAN SECTIO CAESARIA - Maria NSW Kause; Yanita Trisetiyaningsih; Anastasia Suci Sukmawati (MEDIA ILMU KESEHATAN, 2016)
Background: Lactation onset is a term of multiplying breast milk until the release of breast milk for the first time. It is also perceived by mothers as a bit hard breast, inflammed, and full of breast milk or the release of colostrum. Colostrum is the first liquid secreted by breast milk gland since the first day until the fourth day of labour. One of the factors that influences lactation onset is labour methods. Mothers who undergo sectio caesaria surgery will experience pain and prolonged effects of anesthesia compared to mothers with normal labors. Objective: To investigate the difference of colostrum releasing onset in post partum mothers with normal labors and sectio caesaria in Panembahan Senopati General Hospital, Bantul. Method: This study was quantitative with cross sectional design. The number of samples were 80 respondents selected with purposive sampling technique. Study instrument was observational sheets. Data analysis applied Mann-Whitney test. Result: The majority of respondents who had normal labors and sectio caesaria experienced different colostrum onset. In normal labors, the time of colostrum release was 1 day. In sectio caesaria labors, the time of colostrum release was 2 days. The average duration of post partum mothers with normal labors was 13,6 hours and post partum mothers with sectio caesaria was 22,6 hours. The result of Mann-Whitney test was that there was a difference between colostrum release onset of post partum mothers with normal labors and sectio caesaria with p-value of 0,001 (p<0,05). Conclusion: Colostrum onsets were different in normal labors and sectio caesaria labors. Keyword: Colostrum, Normal labors, Sectio Caesaria labors.